(untitled) (Semiárida, 2025)
The objective of this study was to evaluate the ability of climate change models to simulate bioclimatic frost indices in Santa Rosa La Pampa Argentina. Daily minimum temperatures observed and simulated by the CNRM (Centre National de Recherches Météorologiques), CSIRO (Commonwealth Scientific and Industrial Research Organisation), MRI (Meteorological Research Institute), and CMCC (Centro Euro-Mediterraneo per I Cambiamenti Climatici) climate models of the Coupled Model Intercomparison Project Phase 5 (CMIP5) were used. The CNRM and CSIRO models simulated first and last frost days that were within the range of observed first and last frost days during the period 1977–2010. The MRI and CMCC models simulated first and last frost days outside the range of observed days. The mean first and last frost dates simulated by the CNRM, CSIRO, and CMCC models did not differ from the observed dates. The observed variability in mean dates was adequately simulated by the CNRM and CSIRO models, but not by the MRI and CMCC models. The observed mean frost-free period did not differ from that simulated by the CNRM and CSIRO models, but did differ from that simulated by the MRI model. The CNRM and CSIRO models best simulated extreme frost dates (first and last) and the average number of frost days per year. Overall, the CNRM and CSIRO models adequately simulated daily minimum temperatures and bioclimatic frost indices in the western Pampas region of Argentina during the period 1977–2010. These results allow to conclude that the minimum temperature projections from the CNRM and CSIRO models can be used to study the future evolution of bioclimatic frost indices and their variability in the context of different climate change scenarios.